International Research Experiences in the Development of Minority Scientists - Davis, Raeshan D.; Wilson-Kennedy, Zakiya S.; Spivak, David (Frontiers in Education, 2021)
Undergraduate research and international experiences are often described as high-impact educational practices beneficial for undergraduate student success and for supporting the development of science identity and intercultural competencies. While several studies have investigated the impact of undergraduate research on students from minoritized groups, fewer studies have focused on their engagement in global experiences, and fewer still have explored their engagement in international research experiences. Drawing on the theoretical frameworks of Science Identity, Social Cognitive Career Theory, and the Intercultural Competence Model, this present study explores the benefits of participating in an international research experience for minority undergraduate scientists. Using a qualitative case study methodology, we examined the evolution of students' science identity, research competencies, and intercultural competence after engaging in a three-month international research opportunity in France and Belgium. We found that after participating in international research, minority undergraduate scientists had: (1) Increased confidence in their science identity and abilities; (2) Gained and strengthened skills necessary to be a successful researcher, (3) Recognized the influence of international exposure on their growth personally and professionally, (4) Expressed how monumental this research opportunity is for all minority students to experience. Our findings suggest substantial benefits from an international research experience on the development of minority undergraduate scientists.